Supplemental palmitic acid and chromium propionate influence production responses during the immediate postpartum in multiparous dairy cows - J.E. Parales-Girón; J.M. dos Santos Neto; G. Andres Contreras; A.L. Lock (Journal of Dairy Science)
ABSTRACT: Forty-eight multiparous Holstein cows were used in a randomized complete block design and assigned to 1 of 4 treatments in a 2 × 2 factorial arrangement of treatments to determine the effects of supplemental palmitic acid (C16:0) and chromium (Cr) on production responses of early-lactation cows. During the fresh period (FR; 1–24 DIM), cows were fed 1 of 4 treatments: (1) a diet containing no supplemental C16:0 or Cr (CON); (2) diet supplemented with an 85% C16:0-enriched supplement (PA); (3) diet supplemented with Cr-propionate (CR); or (4) diet supplemented with a C16:0-enriched supplement and Cr-propionate (PACR). The C16:0-enriched supplement was added at 1.5% of diet DM by replacing soyhulls in the C16:0-supplemented diets, and the Cr-propionate supplement (0.45 mg Cr/kg of diet DM) was administered through the vitamin and mineral mix. During the carryover period (CO; 25–56 DIM), a common diet was offered to all cows to evaluate the carryover effects of the treatment diets. Palmitic acid and Cr supplementation interacted with time during the treatment period, with the supplemented diets increasing the yields of ECM, 3.5% FCM, and milk fat to a greater extent during the first 2 weeks of lactation compared with CON. By the third week of lactation, C16:0-supplemented diets also increased milk fat yield compared with CR. Additionally, C16:0 and Cr interacted with time in the treatment period to influence plasma insulin, nonesterified fatty acid, and BHB. Overall, C16:0 supplementation increased the yields of milk fat, ECM, and 3.5% FCM, and decreased milk protein content in the treatment period. Overall, Cr supplementation increased the yields of milk, milk protein, and milk lactose in the treatment period. Additionally, Cr supplementation interacted with time, increasing the yields of milk, milk protein, and milk lactose during the CO period. We did not observe treatment differences for DMI and plasma glucose during the FR period, and no treatment effects on BW, BW change, or BCS change in FR or CO periods. In conclusion, C16:0 and Cr supplementation interacted during the early postpartum period to influence milk production responses compared with a nonsupplemented diet. Feeding Cr during the immediate postpartum had a carryover effect, improving milk production responses after ceasing feeding of the treatment diets.